2017
DOI: 10.1021/acs.langmuir.7b01924
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Cadmium Selenide Quantum Dots with Poly(ethylene glycol): Ligand Exchange, Surface Coverage, and Dispersion Stability

Abstract: Semiconductor quantum dots synthesized using rapid mixing of precursors by injection into a hot solution of solvents and surfactants have surface ligands that sterically stabilize the dispersions in nonpolar solvents. Often, these ligands are exchanged to disperse the quantum dots in polar solvents, but quantitative studies of quantum dot surfaces before and after ligand exchange are scarce. We studied exchanging trioctylphosphine (TOP) and trioctylphosphine oxide (TOPO) ligands on as-synthesized CdSe quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…PEG molecules present a zwitterionic character, which is also important for biological interactions. [14][15][16] Over the years, it was revealed that, besides the size-tunable emission, QDs present many other special features for biological application purposes: (i) broad absorption and narrow emission spectra, allowing the use of only one light source to obtain a multicolor labeling; (ii) high quantum yields, providing bright fluorescent images; (iii) low photobleaching rates allowing the follow-up of long-term real-time processes, and (iv) highly active surfaces for conjugations. 2,[17][18][19] In recent years, in vitro and in vivo QD biological applications have remarkably increased due to the outstanding physicochemical properties of these nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…PEG molecules present a zwitterionic character, which is also important for biological interactions. [14][15][16] Over the years, it was revealed that, besides the size-tunable emission, QDs present many other special features for biological application purposes: (i) broad absorption and narrow emission spectra, allowing the use of only one light source to obtain a multicolor labeling; (ii) high quantum yields, providing bright fluorescent images; (iii) low photobleaching rates allowing the follow-up of long-term real-time processes, and (iv) highly active surfaces for conjugations. 2,[17][18][19] In recent years, in vitro and in vivo QD biological applications have remarkably increased due to the outstanding physicochemical properties of these nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…For HS-PEG-NR, a second effect comes into play, which is the bulkiness of the PEG-moiety. This limits the number of surface ligands bound to the surface [60] and leads to an increasing ratio between electron traps due to undercoordinated Cd 2+ and hole traps induced by the thiolate group binding to the surface. This leads to a further decrease in Φ PL500.…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…This introduces surface electron traps, ultimately changing the exciton recombination kinetics. For sub-2-nm CdSe QDs, it has been shown that less than 4 PEG molecules per QD adsorbed to the surface [60] (it has to be noted that the ligand exchange protocol differs from the one used in the report at hand). The longer lifetime, on the other hand, represents the exciton recombination dynamics similar to MUA-NR (with a similar k rad = 2.2 × 10 11 s −1 ).…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…To exchange ligands on the surface of NPs, the concentration and surface affinity of the new molecules should be higher than the concentration and affinity of the original ligand (Karakoti et al 2015). The ligands often used for surface modification to obtain hydrophilic, non-aggregating NPs include polymers (e.g., polyethylene glycol (Liu and Luo 2014;Wenger et al 2017)), amines, phosphines, or compounds containing thiol groups (Lee et al 2010) (such as 3-mercaptopropionic acid and its derivatives (Liu and Luo 2014), glutathione (Wang et al 2012), dihydrolipoic acid (La Rosa et al 2017)).…”
Section: Introductionmentioning
confidence: 99%